Structural victimisation and trafficking in people in Serbia: Coping strategies and criminalisation risks - Nikolić-Ristanović Vesna (Temida, 2008)
This paper tends to explore the relationship between structural victimisation and criminal behavior of people traffickers in Serbia. Looking for conditions under which people in transition and war affected societies create individual choices and motivations, the author attempted to contribute to better understanding of trafficking in people in Serbia, as the form of organized and professional crime, as well as survival strategy. The main theoretical departure of the analysis is economic approach to crime as well as concept of organized crime as criminal enterprise, which represents illegal counterpart of the legal enterprise. Trafficking in people is explored primarily from the prospective of labor market as well as criminal enterprise where division of jobs, status and power is organized in the similar way as in legal enterprise. In the concluding part, possible social responses are mapped which may be considered as alternatives or supplements to penalties for low level people traffickers.